Interleukin-1 receptor antagonist (IL-1RN) and interleukin-1B gene polymorphisms in Turkish patients with rheumatoid arthritis - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2006)
Objective Interleukin I (IL-1) family is composed of two agonists, IL-1 alpha and IL-1 beta and IL-1 receptor antagonist, IL-1Ra. The purpose of this study was to determine the relationship between polymorphisms of IL-1 receptor antagonist (IL-1RN), IL-1B promoter and IL-1B exon 5 genes and susceptibility to rheumatoid arthritis (RA) in Turkish population. Methods Polymerase chain reaction (PCR) was used to determine the genotype of the IL-1RN for 94 RA patients and 104 healthy controls. Genotyping of IL-1B polymorphisms at positions -511 (C/T) and +3953 (C/T) was detected by PCR followed restriction fragment length analysis. Results There was no significant difference in IL-1RN genotype and allele distributions between RA and the control groups. In addition, no significant association was observed in the allelic frequency (C or T) of IL-1B promoter (-511) between RA patients and the controls (P = 0,118), but the genotype distribution of 1/2 (C/T) at position -511 showed a significant difference (P = 0,038). Also, 2/2 genotype (T/T); (P = 0,028), and allele 2 (T) distribution (P = 0,011) of IL-1B (+3953) showed significant differences between RA patients and the control groups in the study population. Conclusion These results imply that 2/2 (T/T) genotype or allele 2 (T) of IL-B (+3953) are susceptibility factors for RA in Turkey. Also, 1/2 genotype (C/T) of IL-1 -511 can play a protective role for RA.
Keywords: 1L-1B and IL-1RN polymorphism; rheumatoid arthritis; SYSTEMIC-LUPUS-ERYTHEMATOSUS; DISEASE-ACTIVITY; TANDEM REPEAT; PLASMA-LEVELS; ASSOCIATION; POPULATION; IL-1-BETA; SECRETION; SEVERITY; TURKEY